Modeling the Potential of Tsunami Hazard in Labuan Bajo Towards A Disaster-Resilient Tourism Area - Mardi Wibowo (Faculty of Geography, Universitas Gadjah Mada, 2022)
In 2019, Labuan Bajo was designated a super-priority tourism destination, but this area is prone to earthquakes and tsunamis. The potential threats of disasters need to be considered when developing the tourism sector. Therefore, this study aims to determine the height and arrival time of tsunami waves based on a worst hypothetical scenario on the north coast of Labuan Bajo and its surroundings. The method used was numerical modelling with open source software TUNAMI F1, which calculated the wave propagation based on linear equations in spherical coordinates based on worst scenarios. The results showed that the Flores back-arc thrust earthquake caused a reasonably high tsunami with a fast arrival time at Labuan Bajo. The wave height of the tsunami around Labuan Bajo, Rinca, and Komodo Island is at least 3 m, but it reaches 8-9 m under certain conditions. Furthermore, its arrival time on the coast of Labuan Bajo is less than 2.5 minutes. This is much faster than those in Aceh (2004), Pangandaran (2006), and Palu (2018). Even though the early warning came 5 minutes after the earthquake, a high level of preparation and awareness is required to create a disaster-resilient tourist area in Labuan Bajo.